The Importance of Sustainable Design in Product Development - Yingchao Feng (Innovation in Science and Technology, 2025)
This study delves into the significance of sustainable design in product development, emphasizing its pivotal role in addressing global environmental issues. Through literature review, the research outlines the definition, principles, and application of sustainable design at various stages of product development. Case studies reveal how companies like Apple and Tesla have achieved environmental benefits and business success through sustainable design practices. The findings indicate that government policies, technological innovation, and consumer awareness are significant factors driving the development of sustainable design. The study offers practical recommendations for policymakers and business managers to promote the wider application of sustainable design principles. Additionally, the study points out potential directions for future research, including cross-cultural adaptability, the application of emerging technologies, and the impact on small and medium-sized enterprises. The conclusion emphasizes that sustainable design is not only a reflection of corporate social responsibility but also a strategic choice for achieving long-term business success.